Responses of Clusterbean to Soil Salinity - Lahiri, A N; Garg, B K; Kathju, S; Vyas, S P; Mali, P C (Annals of Arid Zone, 2016)
Suitability of growing rainfed c1usterbean in lands under summer fallow (after growing wheat with saline ground water) was evaluated through a study of alterations in the performance, N-P-K uptake and metabolism at 0,2,4,6,8 and 10 mmhos cm-1 of soil salinity. Final plant growth and seed yield significantly reduced only at 6 mmhos cm-1 and above. However, the adverse effects of salinity on the levels of leaf metabolites at the pre-flowering stage were discernible at a lower salinity level (4 mmhos cm-1 and above). Activities of different enzymes (i.e. nitrate reductase. protease, peroxidase, acid and alkaline pyrophosphatases) displayed variable sensitivity to salt concentration (2 to 6 mmhos cm-1). The causes of disparate influence of salt concentrations on growth, yield and metabolic parameters have been discussed. Increasing salinity progressively increased the Na concentration and uptake in the shoot tissue without causing significant changes in the N, P and K concentrations. But their uptakes were reduced due to the decline in dry matter production. Taking all facts into consideration. crop has been deemed suitable for cultivation in salt affected areas under summer fallow.